The magnitude of healthcare professionals' turnover intention and associated factors during the period of COVID-19 pandemic in North Shewa Zone government hospitals, Oromia region, Ethiopia, 2021 - Benayew, Mengistu; Hailu, Dejene; Gizaw, Berhanu; Zerihun, Lidya; Zerihun, Mehiret; Liknaw, Tiliksew; Ayenw, Muluken; Shukure, Rebik; Bekele, Kumera; Worku, Abera (Frontiers in Health Services, 2022)
Background: Healthcare professional turnover and shortages are perceived as a global issue affecting the performance of healthcare organizations. Studies show that coronavirus disease has physical and psychological effects on health care workers. This study assessed the magnitude of turnover intention and related factors during the COVID 19 pandemic. Methods: A hospital-based cross-sectional study of 402 health care professionals working in the North Showa Zone was conducted from February 1st to February 30th, 2021. The data was collected using a self-managed structure questionnaire, entered into Epi Data version 3.1, and exported to SPSS version 25 for further analysis. We performed a logistic regression analysis to identify factors related to healthcare professionals’ turnover intention. Finally, the data was displayed in frequency, percentage, and summary statistics. Result: A total of 363 health care professionals participated, with a response rate of 90.3% and 56.7% aimed at leaving their workplace. Single marital status (AOR: 3.926; 95% CI: 1.961; 7.861), completion of obligatory service years (AOR: 0.287; 95% CI: 0.152, 0.542), dissatisfied with the training opportunities (AOR: 2.407) 95% CI: 1.232, 4.701), no established family (AOR: 2.184; 95% CI: 1.103, 4.326), dissatisfied with organizational decisions process (AOR: 0.483; 95% CI: 0.250, 0.932), low continuous organizational commitment (AOR: 0.371; 95% CI 0.164; 0.842) and non-promoting work environment (AOR: 2.079; 95% CI: 1.199, 3.607) were independent predictors of turnover intention. Conclusions and recommendations: The magnitude of turnover intention was high. Strategies that improve the working environment, organizational commitment, and organization’s decision-making and professional development opportunities should be implemented to decrease the rate of turnover intention.